The use of gender-neutral language: a matter of inclusion or a political bias? - GOUVEIA, Alef Jose Pinheiro (2024)
This article main purpose is to present a reflection that aims at elucidating two perspectives concerning the use of the gender-neutral pronoun in the English language. The first angle seeks to address the positions of some authors who oppose the adaptation and use of gender-neutral language in the context of non-binary individuals, as well as to discuss how this adaptation could impact the prescriptive norms of the English language. While the second perspective aims at clarifying the position of authors and activists opposed to sexist language, taking into account the replacement of pronouns such as “he” and “she” with “they”. The methodology consists of reviewing the literature about gender theories and the use of gender-neutral pronouns. The research approach is mainly bibliographic and critical, the main aspect of this type or research is to raise awareness on the topic studied. The research was made through articles, documents, videos and, interviews about the topic. In order to achieve the goal proposed, the article is based on theoretical contributions from authors such as Butler (1990); Helgeson (2017); Pasqualini (2021); Köcher (2021); Murray (2019), among others. After the literature review and reflection, it was possible to realize that some proponents argued that language should not be used as an instrument of discrimination, and therefore defend the appropriateness of pronouns for individuals who identify with a fluid or non-binary gender.